Influence of rapid weight loss on hematological parameters in national-level wrestlers - Roklicer, R.; Manojlovic, M.; Maksimovic, N.; Obradovic, A.; Trivic, T.; Drid, P. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
Purpose Rapid weight loss (RWL) is well-known phenomenon amongst wrestlers. It is characterized by a reduction of ~5% of body weight during the last week before the competition, with the aim of increasing the probability of winning against a potentially lighter athletes. Along with traditional weight loss procedures, competitors usually attend high intensity sport-specific training (HISST) sessions to facilitate the weight reduction. The aim of this study was to determine the influence of RWL together with HISST and the impact of HISST without RWL on hematological parameters in wrestlers.